Efektivitas Kinerja Pemerintah Kelurahan Dalam Program Pemberdayaan Kebersihan Lingkungan - Sinima Luahambowo; Irwan Nasution; Agung Suharyanto (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2022)
Performance effectiveness aims to determine the perfect target in accordance with the goals that have been set from the start. The problem is focused on environmental cleanliness in Sukaramai I Village, Medan District, which is concerning, because of the ignorance of residents in protecting the environment and disposing of rubbish carelessly. In order to approach this problem, a theoretical reference from Bernardin Russel in Sumardjo (2018: 200) is used. The data were collected through interview, observation, library and document data collection techniques, and were analyzed using narrative qualitative methods. The purpose of the research in this case means: to describe the effectiveness of the performance of the sub-district government in the environmental hygiene empowerment event in the Sukaramai I Medan Area village. to describe the factors inhibiting the effectiveness of the performance of the sub-district government at the environmental hygiene empowerment event in the Sukaramai I Medan Area. This study concludes that the results of the study show that the performance of the Sukaramai I Medan Area kelurahan in the effectiveness of the kelurahan performance in the environmental hygiene empowerment program is said to be good and effective.